Midline Skull Base Surgery - Cappabianca, Paolo; Cavallo, Luigi Maria; de Divitiis, Oreste; Esposito, Felice (Springer International Publishing : Imprint: Springer, 2016)
This richly illustrated book offers detailed, step-by-step guidance on surgical approaches and techniques in patients with midline tumors of the skull base. Access routes are described from both endoscopic and microscopic standpoints, via different approaches, in order to provide a 360-degree overview of contemporary midline skull base surgery. For each pathology, the multiple surgical options and their specific indications are clearly presented, with inclusion of neuroradiological images, an anatomical dissection study, and operative images and videos. The book is intended for surgeons who wish to acquire knowledge and experience in skull base surgery employing endoscopic endonasal and microsurgical transcranial techniques. It is exceptional in providing an integrated perspective that encompasses traditional microsurgical approaches and the most recent endoscopic ones, with definition of the indications for and limitations of both options.